Leadership, Intrinsic and Extrinsic Motivation on Knowledge Transfer in Hasanuddin University - Nurwahyu Islamiati; Sumardi Sumardi; Wardhani Hakim (Universitas Negeri Makassar, 2023)
The goal of knowledge management is of course to utilize intellectual assets in achieving better organizational performance in accelerating the attainment of goals. Public organizations are often faced with changes in policies, program or regulations that may affect the knowledge required. This uncertainty can hinder an organization’s ability to plan for and transfer knowledge relevant to the change. What is the relationship between leadership (Lds), intrinsic motivation (InMt) and extrinsic motivation (ExMt) on knowledge transfer (KTrs)? There are still few researchers who explore this question, especially in the sphere of public organizations. The types of data that will be used in this study are qualitative data and quantitative data. The population and sample in this study were all employees at the Financial Administration Bureau, Hasanuddin University. The analysis technique used is multiple linear regression analyisis. The results showed that Lds, InMt, and ExMt had an impact on KTRs. Effective leadership practices that promote knowledge transfer, along with fostering that promote knowledge transfer, along with fostering InMt and ExMt can contribute to KTRs and facilitate knowledge flow throughout the organizations.